The Patient With Right Atrial Thrombus With a Previous History of Double-Chambered Right Ventricular Surgery and Atrial Fibrillation: A Rare Association - Yanhan Xu MM; Mingcheng Gao MM; Yajun Zhang MM; Zhan Shi MM; Huiwen Chang MM; Song Jianxiang MD (SAGE Publishing, 2023)
Right atrial thrombosis, which occurs alone, is rare in clinical practice. Its incidence and mechanism are unclear, but susceptibility factors are usually present at its occurrence: ischemic heart disease, heart failure, atrial fibrillation, and chronic kidney disease. Complete isolated right atrial thrombosis rarely occurs. We report here a 47-year-old male patient with a right atrial mass on cardiac ultrasound and chest computed tomography (CT) and a history of previous right heart surgery with type 2 diabetes mellitus and atrial fibrillation, complaining of "chest tightness and shortness of breath after activity for half a month." The patient was admitted to the hospital and underwent right atrial mass resection, and the postoperative pathology showed "right atrial thrombus." As right atrial thrombus is very rare and can be a serious threat to life when it occurs in the heart, the prevention and treatment of right atrial thrombus are very important. Based on the analysis of this case, we believe that for patients with special medical history such as "post right heart surgery and atrial fibrillation," we need to be vigilant for atrial thrombosis.